Crystal structures of SIRT3 reveal that the α2‐α3 loop and α3‐helix affect the interaction with long‐chain acyl lysine. Issue 17 (24th August 2016) - Gai, Wei; Li, He; Jiang, Hualiang; Long, Yaqiu; Liu, Dongxiang
Abstract : SIRT1‐7 play important roles in many biological processes and age‐related diseases. In addition to a NAD + ‐dependent deacetylase activity, they can catalyze several other reactions, including the hydrolysis of long‐chain fatty acyl lysine. To study the binding modes of sirtuins to long‐chain acyl lysines, we solved the crystal structures of SIRT3 bound to either a H3K9‐myristoylated‐ or a H3K9‐palmitoylated peptide. Interaction of SIRT3 with the palmitoyl group led to unfolding of the α3‐helix. The myristoyl and palmitoyl groups bind to the C‐pocket and an allosteric site near the α3‐helix, respectively. We found that the residues preceding the α3‐helix determine the size of the C‐pocket. The flexibility of the α2‐α3 loop and the plasticity of the α3‐helix affect the interaction with long‐chain acyl lysine. Abstract :